Neuroimmune interactions and their roles in neurodegenerative diseases - Bai-Rong Chen; Ting Wu; Ting-Hui Chen; Yun Wang (Fundamental Research, 2024)
The nervous system possesses bidirectional, sophisticated and delicate communications with the immune system. These neuroimmune interactions play a vitally important role in the initiation and development of many disorders, especially neurodegenerative diseases. Although scientific advancements have made tremendous progress in this field during the last few years, neuroimmune communications are still far from being elucidated. By organizing recent research, in this review, we discuss the local and intersystem neuroimmune interactions and their roles in Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis. Unveiling these will help us gain a better understanding of the process of interplay inside the body and how the organism maintains homeostasis. It will also facilitate a view of the diseases from a holistic, pluralistic and interconnected perspective, thus providing a basis of developing novel and effective methods to diagnose, intervene and treat diseases.